High‐Frequency Correlations Between Winds and pCO2 Change the California Coastal Upwelling System From a CO2 Sink to a Source - Ruiming Song; Tim DeVries; Renjian Li; Adrienne Sutton; Uwe Send; Helena C. Frazão (Geophysical Research Letters, 2025)
Abstract Net sea‐air CO2 flux can be calculated from observations of seawater and atmosphere partial pressure of CO2 (pCO2) and estimates of the gas transfer velocity. Typically, these quantities are calculated at a monthly resolution, which misses potentially important high‐frequency temporal variability. Here, we calculated sea‐air CO2 flux at a 3‐hourly resolution using a 10‐year mooring data set (2011–2020) from the central California coastal upwelling region. We identified a significant flux of CO2 from the ocean to the atmosphere due to a positive correlation between seawater pCO2 and wind speed at timescales of hours to days, particularly during the late spring and early summer upwelling season. Accounting for this variability changes the region from a net sink to a net source of CO2 to the atmosphere. These findings imply that CO2 fluxes computed from monthly‐resolution data may miss important shorter‐term variability that contributes to a net outgassing of CO2 from the ocean.